English Speaking Skill Management Through Administration Image Media Industry - Ganjar Winata (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2023)
English speaking ability of seventh-grade students of Bina Mulya junior high school Bandar Lampung from year to year is still low. Based on the observations obtained data, the average value of students’ English learning outcomes is still relatively low. In teaching and learning activities, there is often a lack of student interest and motivation in learning, and this can be caused by inadequate learning facilities that cause boredom for students to learn. This is where the teacher is required to be able to train himself to be skillful in developing his teaching system and be accustomed to providing positive reinforcement and response because the ability of students’ absorption is different. After using the image media, students are more active. These student activities cause student learning outcomes to increase in each cycle. The increasing average value of student learning outcomes in learning activities can show this. So it is concluded that using image media in learning English can increase the average student learning outcomes, especially speaking skills and procedures. Also, the management of image media in learning is very influential on the activity and motivation and the value of student learning outcomes.